2020
DOI: 10.3390/insects11040227
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Functional Diversification of Lipases in the Endoparasitoid Pteromalus puparum (Hymenoptera: Pteromalidae) by Genome-scale Annotation and Expression Analysis

Abstract: Lipases play essential roles in digestion, transport, and processing of dietary lipids in insects. For parasitoid wasps with a unique life cycle, lipase functions could be multitudinous in particular. Pteromalus puparum is a pupal endoparasitoid of butterflies. The female adult deposits eggs into its host, along with multifunctional venom, and the developing larvae consume host as its main nutrition source. Parasitoid lipases are known to participate in the food digestion process, but the mechanism remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…In this study, we identified a total of 481 lipase genes in 12 fig wasp species belonging to neutral, acid, lipase3, GDSL and HSL lipase gene families. Lipase2 was not found in fig wasps, which was consistent with the lack of lipase2 in other insects [ 14 ]. This is the first investigation of the lipase gene family in fig wasps.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In this study, we identified a total of 481 lipase genes in 12 fig wasp species belonging to neutral, acid, lipase3, GDSL and HSL lipase gene families. Lipase2 was not found in fig wasps, which was consistent with the lack of lipase2 in other insects [ 14 ]. This is the first investigation of the lipase gene family in fig wasps.…”
Section: Discussionsupporting
confidence: 80%
“…Compared with two phylogenetic related N. vitripennis and A. mellifera , we can see the number of lipases in N. vitripennis (62) was close to that of P. tridentata . However, the A. mellifera (26) had the least number of lipases in the reported insects [ 14 ]. The expansion and contraction analysis also revealed that A. mellifera as well as all the PFWs had a significant contraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations